POLA PENGEMBANGAN DAN EVALUASI KURIKULUM PENDIDIKAN AGAMA ISLAM - H.M. Nasron HK (Nuansa : Jurnal Studi Islam dan Kemasyarakatan, 2015)
The problem discussed in this paper  is how the Islamic education curriculum development in schools using the curriculum framework development disciplines. Systematically,  this paper  discusses the significance of PAI curriculum, curriculum components, approach to curriculum development, curriculum development base,  steps  in curriculum organization, curriculum organization, competency-based  curriculum. The authors assume that Islamic religious education (PAI) as the subjects need to be developed to respond to the demands and dynamics of the community